2008
DOI: 10.1242/jeb.010587
|View full text |Cite
|
Sign up to set email alerts
|

New developments on gill innervation: insights from a model vertebrate

Abstract: SummaryThe fish gill is a highly specialized and complex organ that performs a variety of important physiological functions. In this article, we briefly review the innervation of important structures of the branchial region, such as the gill filaments, respiratory lamellae and pseudobranch, and discuss the physiological significance of this innervation within the context of homeostatic functions of the gill, such as oxygen sensing and ion regulation. Studies in zebrafish utilizing techniques of confocal micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 70 publications
(131 reference statements)
1
17
1
Order By: Relevance
“…Previous studies on ASICs in fishes have suggested that they are primarily associated with neuronal tissue and sensory cells (27,35,42,46). In adult and developing zebrafish, morphological studies using confocal immunofluorescence techniques demonstrated that gill MRCs come into direct contact with nerve fibers in the basolateral region (21,22). However, in our study, ASIC4 protein was clearly localized to the apical region of the MRCs, as demonstrated by three-dimensional reconstruction of con- focal images.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Previous studies on ASICs in fishes have suggested that they are primarily associated with neuronal tissue and sensory cells (27,35,42,46). In adult and developing zebrafish, morphological studies using confocal immunofluorescence techniques demonstrated that gill MRCs come into direct contact with nerve fibers in the basolateral region (21,22). However, in our study, ASIC4 protein was clearly localized to the apical region of the MRCs, as demonstrated by three-dimensional reconstruction of con- focal images.…”
Section: Discussioncontrasting
confidence: 57%
“…For all flux experiments, fish were transferred to individual darkened 60-ml flux chambers, supplied with a constant flow of aerated low-ionic-strength, low-pH water, and acclimated to the chambers for 24 h prior to experimentation. Unidirectional Na ϩ influx was measured using radiolabeled 22 Na, as described previously (12). Briefly, flow of water to chambers was turned off, 0.1 Ci/l 22 Na was added to each chamber and allowed to mix for 5 min, and either the DMSO control (0.05% DMSO) or pharmacological agents dissolved in DMSO were added to the chambers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the distally located NECs are innervated, they are presumed to be fully functional O 2 chemoreceptors. The nerve fibres innervating the lamellar NECs are protrusions of the branchial nerves which branch from bundles within the filament to innervate the lamellae (Jonz and Nurse, 2008). Interestingly, there appeared to be little, if any, nerve fibres present within the ILCM, itself, a finding which is consistent with the apparent absence of NECs on the outer edge of the ILCM.…”
Section: Branchial Nec Distribution In Fish With or Without An Ilcmmentioning
confidence: 51%
“…The gills, and presumably the branchial ICs, are innervated by the IX and X cranial nerves 7,[23][24][25] . These nerves carry both efferent and afferent inputs to and from the gill, respectively.…”
Section: Discussionmentioning
confidence: 99%